Legal Philosophy's View of the Role of Advocate Professional Ethics as an Honorable Profession in Carrying Out Good Law Enforcement - Ade Rizki Saputra; Davidescu Cristiana Victoria (Formosa Journal of Sustainable Research, 2023)
The lawyer profession plays a crucial role in maintaining integrity and justice in the legal system. From the perspective of legal philosophy, the professional ethics of advocates is a deep and complex foundation. Several philosophical views, such as utilitarianism, deontology, and contractualism, provide a framework for understanding advocate ethics. The utilitarian view emphasizes the importance of achieving the best outcome for society as a whole, which can create ethical dilemmas when advocates are faced with controversial cases. In contrast, deontology emphasizes the moral obligations that advocates must follow, which can give rise to conflicts between obligations to clients and society. Contractualism links the ethics of advocates to the moral agreements that underlie the legal system, emphasizing their responsibility for better social change. Advocate ethics is also closely related to the concept of social justice, where advocates must ensure that the law is applied fairly, regardless of individual background. In addition, in dealing with ethical conflicts in practice, advocates must refer to the ethical principles of their profession as a guide. Advocates' ethics not only underlie their duties as legal representatives, but also involve moral considerations about how their actions may affect society as a whole. This is a very important foundation in maintaining professionalism and carrying out their role as law enforcers